PENENTUAN KADAR LOGAM KADMIUM (Cd) PADA TANAMAN KANGKUNG AIR (Ipomoea aquatica Fork.) DAN SEDIMEN SEBAGAI MEDIA TUMBUHNYA DI SAMARINDA - Indary, Melati Deshy; Susanto, Dwi; Sudrajat, Sudrajat (Jurusan Biologi, Fakultas Matematika dan Ilmu Pengetahuan Alam, 2016)
The purpose of this study is to determine of the concentration of heavy metal Cd in water spinach plants and in the sediments as a its growth medium. The sampling is done at several locations of water spinach suppliers such as Benanga reservoirs, Asparagus Bengkuring and the rear outdoor area of FKESMAS Unmul. Cd contect was analyzed using Atomic Absorption Spectrophotometry (AAS).The results showed that the content of Cadmium (Cd) in water spinach plants, which were taken from Benanga reservoir is 0.0022 ± 0.0003 mg Kg-1; Asparagus Bengkuring is 0.0021 ± 0.0004 mg Kg-1 ; the Rear outdoor area of FKESMAS Unmul is 0.0016 ± 0.0003 mg/kg and the average level of Cadmium in sediment, which were taken from reservoir Benanga is 0.442 ± 0.336 mg Kg-1; Asparagus Bengkuring is 0.513 ± 0.317 mg Kg-1; the Rear outdoor area of FKESMAS Unmul is 0.08 ± 0.039 mg Kg-1. The level of Cadmium in water spinach plant ranges from 0.0016 to 0.0022 mg Kg-1, which is under the limit determined by the BPOM (0.2 mg Kg-1). The level Cadmium in the plant is determined by the levels of heavy metals in sediment with regression coofficient 0.001X Y = 0.001x + 0.001) at significance level 0.008. The conclusion of this research is the levels of heavy metals in the water spinach plant originating from several suppliers locations in Samarinda meets the qualifications of hygienic vegetables set by BPOM. And, it also concluded that the level of heavy metals in water spinach is specified by the level of heavy metal in its sediment.